2010
DOI: 10.4314/ajbr.v7i2.54071
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sub-lethal effects of copper to the african catfish (<i>clarias gariepinus</i>) juveniles

Abstract: Lethal and sub-lethal effects of copper on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 4 publications
4
45
1
3
Order By: Relevance
“…The growing rate of industrialization is gradually leading to contamination and deterioration of the environment and pollution is likely to reach disturbing levels. Studies have shown that industrialization and pollution are positively correlated (Walsh, 2000;Olaifa et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The growing rate of industrialization is gradually leading to contamination and deterioration of the environment and pollution is likely to reach disturbing levels. Studies have shown that industrialization and pollution are positively correlated (Walsh, 2000;Olaifa et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The effects of different toxicants on the aquatic fauna, particularly fish have received attention of many investigators [2,4,11,17,15,23,[28][29][30] as among animal species, fish are the inhabitants that cannot escape from the detrimental effects of these pollutants [8,22]. The toxicants like heavy metals after entering into aquatic environment accumulate in the tissues and organs of aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The beaker was then placed on water bath and boil at a temperature of 120 0 C for two hours to reduce the volume to 3cm 3 .Then 20cm 3 of distilled water was added and the solution was allowed to cool. The resultant mixture was filtered using Whatmann filter paper into a 50cm 3 volumetric flask, diluted to the mark with distilled water, transferred into a plastic sample bottle and labeled accordingly [14].…”
Section: Digestion Of Samplementioning
confidence: 99%